1331. Reducing Inpatient Antimicrobial Treatment Duration for Febrile Infants through Implementation of Rapid Diagnostic Testing and Clinical Risk Definition. (31st December 2020) - Erdem, Guliz; Watson, Joshua; Buckingham, Don; Ramilo, Octavio; Barson, William J
Abstract: Background: The management approach to febrile infants remain challenging. Despite new advances in rapid diagnostic testing, febrile infants with a viral infection could receive prolonged antimicrobial treatment due to concerns for co-existing serious bacterial infection (SBI). We sought to decrease the duration of antibiotic treatment in febrile infants less than 8 weeks of age hospitalized on inpatient infectious disease service following sepsis evaluation, who have enterovirus, parechovirus, or respiratory viruses detected, from average 30 hours to 24 hours and sustain for six months. Figure 1. Antibiotic Treatment Duration of Infants Underfoing Evaluation for Sepsis Figure 2. Length of Stay in Infants Underfoing Sepsis Evaluation Methods: A new management guideline that defined "low-risk" infants, as well as inclusion and exclusion criteria, was created to monitor the accurate duration of parenteral treatment and length of hospitalization. Respiratory viruses were detected by a multiplex PCR assay. We created a QlikSense App for further clinical characterization of patients and follow-up. This management guideline was adapted as a quality improvement division initiative. Control charts were used to assess the impact of the interventions. Figure 3. Readmissions in Infants Underfoing Sepsis Evaluation Results: The management guideline was developed and implemented by pediatric infectious disease faculty. Febrile infants < 8 weeks of age were included if they had both documented viral infections and sepsis evaluation. 178 infants were admitted with fevers in 2018 and 148 infants were admitted in 2019. The mean inpatient antibiotic treatment duration decreased from 27.7 hours in 2018 to 24.9 hours in 2019 (P > 0.05) (Figure 1). There was no significant difference in length of hospitalization or 30-day readmission rates (Figure 2 and 3). There was no reported readmission for SBI. Conclusion: Antibiotic treatment could be discontinued in clinically stable infants with a documented viral infection after 24 hours of negative blood, CSF, and urine bacterial culture incubation so as not to receive unnecessary prolonged inpatient treatment that may increase side effects. In addition to possible decreased treatment side effects our protocol led to decreased patient care costs with no documented changes in readmission rates. Disclosures: Octavio Ramilo, MD, Bill & Melinda Gates Foundation (Grant/Research Support)Janssen (Grant/Research Support, Advisor or Review Panel member)Medimmune (Grant/Research Support)Merck (Advisor or Review Panel member)NIH/NIAID (Grant/Research Support)Pfizer (Consultant, Advisor or Review Panel member)Sanofi/Medimmune (Consultant, Advisor or Review Panel member)